Field effect in molecule-gated switches and the role of target-to-receptor size ratio in biosensor sensitivity - Garrote, Beatriz L. [UNESP]; Fernandes, Flavio C.B. [UNESP]; Cilli, Eduardo M. [UNESP]; Bueno, Paulo R. [UNESP] (Elsevier, 2019)
We demonstrated here that molecular redox films are electrochemical capacitive devices possessing specific field effect in which molecular moieties within films act as sensitive gates. We confirm that the field effect present in these redox switches is suitable in detecting, in a label-free manner (without needs of redox probe in the biological samples), biomarkers of essential importance for dengue, heart risks and inflammation, Parkinson's disease and tumors. Though the sensitiveness is high, it is governed by Thomas Fermi screening and thus depends on the target-to-receptor size ratio. Thus, we also demonstrated how this target-to-receptor size ratio affects the sensitivity. We concluded that the smaller the biological receptor the greater the sensitivity. Consequently, a larger molecular target associated with a smaller receptor provides a considerable (predictable) improvement of the sensitiveness.
Keywords: Debye screening; Molecular electrochemistry; Molecular transistor; Quantum capacitors; Redox switches; Thomas-Fermi screening